The Impact of Teacher’s Enthusiasm on Students’ Engagement in Learning English as a Foreign Language The Case Study of First Year Middle School Class-Oukid Allal- Laghouat - Chabira, Imane; Korichi, Souhila (Faculty of Letters and Foreign Languages Department of English, 2016)
This research examines the impact of teacher’s enthusiasm on students’ engagement in learning English as a foreign language. This study attempts to investigate and analyse the relationship between teacher’s enthusiasm and first year middle school pupils’ engagement in EFL classes. This work depends on one instrument of investigation which is the questionnaire as a measuring tool to set further information about the actual learning environment. This questionnaire aims to assess the level of the pupils’ engagement as well as their perception of their teachers’ enthusiasm. It is conducted at Oukid Allal middle school in Laghouat, selecting 120 first year middle school pupils as a sample of a total population of 196 pupils. The sample represents 61%. Results reveal that teaching with enthusiasm influences positively pupils’ engagement in learning English as a foreign language. Findings also show that teacher’s enthusiasm affects more the emotional engagement.